2021
DOI: 10.1021/acs.jmedchem.0c01917
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Atabecestat (JNJ-54861911): A Thiazine-Based β-Amyloid Precursor Protein Cleaving Enzyme 1 Inhibitor Advanced to the Phase 2b/3 EARLY Clinical Trial

Abstract: Accumulation of amyloid β peptides (Aβ) is thought to be one of the causal factors of Alzheimer's disease (AD). The aspartyl protease β-site amyloid precursor protein cleaving enzyme 1 (BACE1) is the rate-limiting protease for Aβ production, and therefore, BACE1 inhibition is a promising therapeutic approach for the treatment of AD. Starting with a dihydro-1,3-thiazine-based lead, Compound J, we discovered atabecestat 1 (JNJ-54861911) as a centrally efficacious BACE1 inhibitor that was advanced into the EARLY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 49 publications
(73 reference statements)
2
24
0
Order By: Relevance
“…BACE1, which is responsible for the N-terminal processing of Aβ, has been investigated as a therapeutic target molecule. Various BACE1 inhibitors, such as verubecestat, umibecestat, and atabecestat have been developed, and their efficacy and pharmacodynamics have been investigated in animal models (Kennedy et al, 2016 ; Neumann et al, 2018 ; Koriyama et al, 2021 ). However, none of them have shown therapeutic effects in clinical trials (Egan et al, 2018 , 2019 ; Novak et al, 2020 ).…”
Section: Preclinical Analyses Of Potential Ad Therapies Using Model Micementioning
confidence: 99%
“…BACE1, which is responsible for the N-terminal processing of Aβ, has been investigated as a therapeutic target molecule. Various BACE1 inhibitors, such as verubecestat, umibecestat, and atabecestat have been developed, and their efficacy and pharmacodynamics have been investigated in animal models (Kennedy et al, 2016 ; Neumann et al, 2018 ; Koriyama et al, 2021 ). However, none of them have shown therapeutic effects in clinical trials (Egan et al, 2018 , 2019 ; Novak et al, 2020 ).…”
Section: Preclinical Analyses Of Potential Ad Therapies Using Model Micementioning
confidence: 99%
“…On the basis of a rational design of the pK a -decreasing approach, thiazine-based BACE1 inhibitors 39 (JNJ-54861911, Atabecestat) with the most promising profile and decreased ER were advanced to further in vivo studies (Figure 15). 107 In the design of phosphodiesterase 10A (PDE10A) inhibitors, a dual substrate PDE that catalyzes the hydrolysis of cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP), two similar structures showed extraordinary differences in blood−brain distributions. Investigators assessed TgCPL inhibitors 40 and 41 in vitro to determine whether they were potential substrates of P-gp.…”
Section: Strategies For Enhancing the Bbbmentioning
confidence: 99%
“… 12 , 13 Elenbecestat (E-2609, Eisai), 14 verubecestat (MK-8931, Merck), 15 and atabecestat (JNJ-911, Janssen) 16 reached phase III clinical trials but failed due to lack of clinical efficacy or observed toxicity. 12 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%